Coronary endarterectomy in myocardial revascularization - Ya. Yu. Visker; D. N. Kovalchuk; A. N. Molchanov; O. R. Ibragimov (Российский кардиологический журнал)
Aim. To compare the immediate outcomes of combined coronary artery bypass grafting (CABG) with coronary endarterectomy (CE) and isolated CABG.Material and methods. This retrospective study included 192 patients with stable angina who underwent myocardial revascularization in the period from January 2016 to August 2018. The patients were divided into 2 groups. Group 1 included patients who underwent combined CABG and CE, while group 2 — patients who underwent isolated CABG. Patients in both groups did not differ in the main preoperative characteristics, with the exception of the incidence of obesity and right coronary artery disease.Results. In-hospital mortality in group 1 was 2,2% (n=2), in group 2 — 2% (n=2). The incidence of perioperative myocardial infarction in group 1 was 1% (n=1) and in group 2 — 0%. There were no significant differences between groups in the following postoperative parameters: in-hospital mortality, perioperative myocardial infarction, need and duration of inotropic support, duration of mechanical ventilation (MV) and need for long-term mechanical ventilation, stroke, arrhythmias, resternotomy for bleeding. In group 1, encephalopathy (11,8%) and respiratory failure (12,9%) were significantly more common.Conclusion. Combined CABG and CE is a safe technique for achieving complete myocardial revascularization in diffuse coronary artery disease, since, in comparison with isolated CABG, there is no increase in the incidence of death and perioperative myocardial infarction. However, in this category of patients, an increase in the incidence of non-lethal, non-disabling cerebral and pulmonary complications should be expected.